(untitled) (Media Kesehatan Masyarakat Indonesia, 2023)
The decrease in capability is caused by work fatigue and the level of error in work will increase. The increase in errors in work will cause the opportunity for work accidents in the industry which is the cause and effect of a work accident. This study aimed to determine solutions to eliminate mental workload from a safety climate based on NOSACQ-50 using the NASA-TLX method at PT. X part of The Batam City field in 2021. This quantitative study uses an analytical design with a cross-sectional approach between NOSACQ-50 to determine safety climate and NASA-TLX Method to determine mental workload based on the safety climate. The objects of this research are all workers of PT. X in 2021, with a sample size of 30 respondents. Statistical analysis used chi-square test. The results of this study show that Mental Workload in PT.X mostly was in moderate Level (73,3%) with the highest workload score was in the physical needs. NASA-TLX shows that Empowerment of Work Safety from Management was the significant factor causing mental stress. It was concluded that mental stress is caused by poor work arrangements. Suggestions for companies is to rotate work in each group of workers, especially riggers so that the workload is evenly distributed, and top management participates and is committed to carrying out OHS programs by directly demonstrating the programs that have been set.